CTAB modified Fe-WO3 as an electrochemical detector of amitrole by catalytic oxidation - Ilager, Davalasab; Seo, Hyngtak; Shetti, Nagaraj P.; Kalanur, Shankara S. (Journal of Environmental Chemical Engineering, 2020)
The increasing health risk associated with the exposure to mutagenic, teratogenic and carcinogenic herbicide in the environment has encouraged a significant interest towards the development of rapid and cheaper detection technologies for the accurate quantification. The present work involves the exploitation of catalytic oxidation of herbicide, amitrole (AMT) at iron doped tungsten oxide (Fe-WO3) nanoparticles and cationic surfactant cetyltrimethylammonium bromide (CTAB) based carbon paste electrode for the sensitive quantification. The working electrode assembly of Fe-WO3/CTAB causes the catalytic oxidation via faster electron transfer compared to bare electrode. Furthermore, the physiochemical properties and thermodynamic properties of AMT were explored. Under the optimized conditions, the modified sensor exhibits good linear detection range (5.0 × 10−8 M to 8.0 × 10−5 M), lower limit of detection (0.82 nM) and limit of quantification (2.82 nM) by square wave voltammetric (SWV) technique. Hence, developed senor showed an intensification of peak current of AMT with significant sensitivity, selectivity and reproducibility for AMT analysis and received acceptable results indicates the application of sensors for the analysis of AMT in water as well as soil samples.
Keywords: Accurate quantifications; Carbon paste electrode; Cationic surfactant cetyltrimethylammonium bromides; Electrochemical detectors; Limit of quantifications; Linear detection ranges; Lower limit of detections; Physio-chemical properties; Amitrole; Catalytic oxidation; Environmental applications; Fe-doped WO3/CTAB/CPE; Voltammetric determination